Perbandingan Efektivitas Media Cetak (Folder dan Poster-Kalender) dan Penyajian Tanaman Zodia terhadap Peningkatan Pengetahuan Masyarakat - L. Marlina; A. Saleh; R.W.E. Lumintang (Jurnal Komunikasi Pembangunan, 2009)
Objectives of research were to determine the combination treatment of printed material (folder media and calendarposter)combined with Zodia plant toward increasing community knowledge in North Bogor sub-district. Design ofresearch was a quasi-experimental design. Sample was chosen in the endemic area of dengue disease (DBD).Sampling design was a separate sample pretest-posttest control group design. Experimental design was a 2x3factorial design. Respondents were totally 90 housewives, divided into six groups. Research result was: (1)effectiveness of printed media can be increased toward phisical media usage; (2) increasing knowledge was veryeffective toward media combination; (3) folder combined with Zodia plant was more effective to increase communityknowledge; Community knowledge was emphasis on utilizing Zodia plant to prevent mosquito as an agent of denguedisease; (4) several characteristic factors were increase community knowledge effectively, (5) innovation factorswere also effectively increase community knowledge. It was concluded that folder media combined with Zodia wasthe most effective media to deliver a message of Zodia plant to increase community knowledge.